The Pullulan Production From Substrate of Sagoo Starch By Pullularia pullulans - Dosis Undjung (Jurnal Teknologi dan Industri Pangan, 2005)
The aim of this research was to recognize the potency of pullulan by Pullularia pullulans from hydrolyzed Sagoo starch as opposed to sucrose. Another objective was to find out a better condition for agitation of pullulan production in a batch fermentation. Sagoo can be found in Kuala Kapuas, Central Kalimantan. Initially sago was made into sago starch. The Sago starch was then hydrolyzed to be used as substrate for pullulan production. As a comparison, sucrose was also used. Pullulan production was carried out by pullaria pullulans, T37A or CBS CYPP using various agitation rate & incubation period. The research showed that increase in agitation resulted in increase in pullulan production. At 100 rpm, the yield was 1.299 g/l while at 150 rpm yield was 1.546 g/l. Strain CBSCYPP also produced more pullulan than T 374. Key words : Pullulan production, Sagoo starch and Pullularia pullulans